Evaluation of the efficacy and treatment-emergent adverse events of deuruxolitinib for moderate to severe alopecia areata: a dose-ranging meta-analysis of 1,372 randomized patients - Kalantan, Mulham; Bashrahil, Bader; Aljuaid, Abdulaziz; Bogari, Hassan; Samarkandy, Sahal; Jfri, Abdulhadi (Frontiers in Medicine, 2025)
IntroductionAlopecia areata (AA) is an immune disease characterized by non-scarring hair loss. With the increasing use of Janus kinase (JAK) inhibitors in immune-related conditions, their potential role in AA treatment is gaining attention. Deuruxolitinib has emerged as a potential treatment for moderate to severe AA. This is the first systematic review and meta-analysis that aims to assess the efficacy of deuruxolitinib in moderate to severe AA.MethodsWe systematically searched Cochrane Central Register of Controlled Trials (CENTRAL), Medline, and ClinicalTrials.gov for relevant data. Deuruxolitinib vs. placebo was evaluated, and efficacy was measured using severity of alopecia tool (SALT) and Hair Satisfaction Participants Reported Outcome (SPRO), with the primary time point of assessment at week 24. Treatment-emergent adverse events (TEAEs) such as increased creatinine kinase (CPK), acne, and headache were specifically assessed at week 28. Effect sizes were presented using mean difference (MD) or risk ratio (RR). Statistical heterogeneity was measured by I2, with a 95% confidence interval (CI) and p-value less than 0.05 considered significant. Risk of bias was assessed using the Revised Cochrane risk of bias tool. Subgroup analysis was conducted for different regimens (8 mg and 12 mg) and TEAEs of interest. This research was registered in PROSPERO (CRD42023417104).ResultsThree randomized controlled trials involving 1,372 patients were included. Deuruxolitinib demonstrated a significant improvement in SALT score change from baseline [MD = −47.26, 95% CI = (−53.47, −41.05), p < 0.00001, I2 = 76%], with a significant number of patients achieving 75% [RR = 93.66, 95% CI = (23.42, 374.65), p < 0.00001, I2 = 0%] and 90% [RR = 65.26, 95% CI = (16.28, 261.58), p < 0.00001, I2 = 0%] improvement from baseline. Patients randomized to deuruxolitinib reported a significant improvement in SPRO [MD = −1.52, 95% CI = (−1.76, −1.27), p < 0.00001, I2 = 69%], with many experiencing more than two points of improvement [RR = 4.98, 95% CI = (3.79, 6.54), p < 0.00001, I2 = 0%]. TEAEs included elevated CPK levels [RR = 2.79, 95% CI = (1.5, 4.99), p = 0.0006, I2 = 0%], headaches [RR = 1.49, 95% CI = (0.98, 6.54), p = 0.06, I2 = 44%], and acne (significant in the 12 mg dose only) [RR = 1.80, 95% CI = (0.84, 3.88), p = 0.13, I2 = 64%].DiscussionIn conclusion, deuruxolitinib shows promising efficacy in treating moderate to severe AA, leading to significant improvements in hair regrowth and patient-reported satisfaction. While certain TEAEs such as increased CPK levels, headaches, and acne (especially at the 12 mg dose), they were generally manageable. Further research and vigilant monitoring for long term safety are necessary before widespread adoption of deuruxolitinib for AA treatment.